Screening the Geographical Origin of Brazilian Wines According their Elemental Composition - Souza, Anderson S.; Fernandes, Andrea Pires; Oliveira Araujo, Rennan Geovanny; Andrade, Rafael Franca; Andrade Vinhas, Ana Claudia (Current Analytical Chemistry, 2017)
Background: Multivariate statistical analyses were used to investigate the mineral contents of wines from the mid-São Francisco River valley, located between the northeastern Brazilian States of Bahia and Pernambuco, with those of wines from Rio Grande do Sul State. Methods: Ten elements (Al, Ba, Ca, Fe, K, Mg, Mn, Na, P, and Zn) were determined by inductively coupled plasma optical emission spectrometry (ICP-OES). The results were applied to Principal Components Analysis PCA) and and Hierarchical Cluster Analysis (HCA). Results: Considering the 28 wine samples analyzed, the elements Ca, Mg, K, and P were found in higher concentrations in the northeastern wines, with average contents of 71.6, 85.5, 632.9, and 191.2 mg L-1, respectively, and concentration ranges of 6.7-132.0, 53.7-120.7, 177.8-1071.9, and 79.5-376.1 mg L-1, respectively. Conversely, the elements Al, Ba, Fe, Mn, Na, and Zn were found in lower concentrations in the northeastern wines, with average contents of 0.53, 0.19, 1.31, 1.47, 0.69, and 0.46 mg L-1, respectively, and concentration ranges of 0.17-1.28, 0.03-0.46, 0.26-2.34, 0.41-2.73, 0.29-1.59, and 0.06-0.95 mg L-1, respectively. Conclusion: Principal component analysis and hierarchical cluster analysis revealed a natural distinction between the wines from the mid-Sao Francisco River valley and Rio Grande do Sul.
Keywords: HCA